The Effect of Dark Chocolate on The Level of Dysmenorrhea Pain in Adolescents at Puskesmas Ibu - Fadila Mubin; Sulistiyah Sulistiyah (International Forum of Researchers and Lecturers, 2026)
Background: Adolescence is a transitional phase marked by biological changes, one of which is menstruation. A common problem during menstruation is dysmenorrhea or lower abdominal pain, which can interfere with quality of life and daily activities. One non-pharmacological effort to address this is consuming dark chocolate, which contains magnesium and triggers the release of endorphins as a natural pain reliever. Methods: This study used a quantitative method with a pre-experimental design through a one-group pretest-posttest design. The research population and sample consisted of 30 adolescent girls experiencing menstrual pain, selected using total sampling technique. Data analysis used the Wilcoxon Test to examine the effect before and after the intervention. Results: Before consuming dark chocolate, the majority of respondents experienced moderate pain (76.7%) and severe pain (16.7%). After the intervention, a significant reduction in pain level occurred, with 90% of respondents falling into the mild pain category and no respondents experiencing severe pain. The mean pain level decreased from 2.07 to 1.20 with a p-value = 0.000. Conclusion: The administration of dark chocolate has a significant effect on reducing the level of dysmenorrhea pain in adolescents at Puskesmas Ibu.